Integration Of Promising Fungicides, Plant Extract And Bio Control Agents For Management Of Root Rot Of Ajwain Caused By Rhizoctonia Solani (Journal of Plant Disease Sciences, 2021)
The field experiments were conducted in research farm at Rajasthan College of Agriculture, Udaipur (Rajasthan) for consecutive season of Rabi 2015-16 and 2016-17 under the objective of to develop integrated management module for against Rhizoctonia solani causing root rot of ajwain. On the basis of in vitro studies, one promising fungicide, plant extracts and one bio control agent were evaluated alone or in combination against R. solani for with each other and result revealed that the most effective combined treatments were Bavistin (0.1%) + Neem oil (0.2%) + T. viride (1 x103cfu) superior in terms of lower mortality (10.75%), higher PEDC (84.75%), higher grain (0.51 Kg/plot) yield and higher per cent increase in grain yield (94.37%) as compare to the individual treatment. The research results show the need for an integrating selective microbial antagonist, plant extracts and fungicide to achieve appropriate management of plant mortality (R. solani) and increase of grain yield in ajwain.
Keywords: Ajwain; Bio control agents; Fungicides; Plant extracts; R. solani